2011
DOI: 10.3892/ijo.2011.1238
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated ephrin-B2 signaling in mammary epithelial cells alters the stem cell compartment and interferes with the epithelial differentiation pathway

Abstract: Abstract. Cancer most probably originates from stem/progenitor cells and exhibits a similar cell hierarchy as normal tissues. Moreover, there is growing evidence that only the stem cells are capable of metastasis formation. We have previously shown that overexpression of a dominant negative ephrin-B2 mutant interferes with mammary gland differentiation and confers a metastatic phenotype to NeuT-induced mammary tumors with an increase in cells with stem/progenitor characteristics. To investigate the role of eph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Repopulation assays revealed that the epithelial cells of mutant ephrin-B2 transgenic epithelial cells are able to repopulate epithelial-free mammary fat pads of normal recipient mice more extensively and faster than those of controls and of native ephrin-B2 transgenic mice, confirming the augmentation of stem cells. Morphologically, these outgrowths exhibited an abnormal basal/luminal compartmentalization and impaired epithelial polarization 73 . These results demonstrate that deregulated ephrin-B2 expression interferes with the regulation of the stem cell niche and leads to a shift in the binary decision pathway during progenitor cell differentiation (Fig.…”
Section: The Involvement Of Eph/ephrin Signaling In Mammary Stem Cellmentioning
confidence: 55%
“…Repopulation assays revealed that the epithelial cells of mutant ephrin-B2 transgenic epithelial cells are able to repopulate epithelial-free mammary fat pads of normal recipient mice more extensively and faster than those of controls and of native ephrin-B2 transgenic mice, confirming the augmentation of stem cells. Morphologically, these outgrowths exhibited an abnormal basal/luminal compartmentalization and impaired epithelial polarization 73 . These results demonstrate that deregulated ephrin-B2 expression interferes with the regulation of the stem cell niche and leads to a shift in the binary decision pathway during progenitor cell differentiation (Fig.…”
Section: The Involvement Of Eph/ephrin Signaling In Mammary Stem Cellmentioning
confidence: 55%
“…Studies conducted to identify the regulation of CSC niche in the maintenance of self-renewal and differentiation in the normal stem cell compartments have shown that generation of expression gradients of different signaling molecules, like WNT, BMP, Eph receptors, and Ephrin-B1 play a role in the intestinal crypt cell homeostasis ( 7 11 ). Eph receptors and Ephrins are also reported for the maintenance of other adult stem cell niches like that of mammary gland, neural, skin and prostate ( 42 44 ). Eph/Ephrin signaling is also shown to be involved in cancer stem cell niche maintenance in leukemia and Glioblastoma ( 45 47 ).…”
Section: Discussionmentioning
confidence: 99%